Pengaruh Perbandingan Eceng Gondok Dan Air Terhadap Penyisihan COD (Chemical Oxygen Demand) Dan Padatan Pada Produksi Biogas tahap Metanogenesis - Nurul Annisa; Sri Rezeki Muria; Adrianto Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Biomass of water hyacinth (Eicchornia crassipes) is a weed plant that is growing very fast. Components of water hyacinth has a high cellulose that potential to be used as raw material for production of biogas by anaerobic fermentation. The purpose of this study to determine the effect of substrate ratio for Chemical Oxygen Demand (COD) removal and solids removal and the maximum process conditions. This process using a 15 liters of batch bioreactor at pH 7 with variation of water hyacinth and water 1: 2, 1: 3, 1: 4 and 1: 5. Observations biogas production is done by measuring the volume of biogas produced each day, while organic matter and solids content by seeking removal efficiency of COD and solids removal. The results showed that COD removal efficiency of the largest in the ratio of 1:2 is 80,85% and the total solids removal efficiency at a ratio of 1:2 was 63.04%, 1:3 was 54.49%, 1:4 was 36.32%, and 1:5 was 31.25%. The largest biogas production substrate ratio of 1: 2 at 23,300 mL and the results of methane analysis using gas chromatography amounted to 11924.56 ppm (1,19%).Keywords: anaerobic, batch, biogas, gas chromatography, water hyacinth